Antioxidant properties and sensory evaluation of microgreens from commercial and local farms - Libo Tan; Holly Nuffer; Jiannan Feng; Shu Hang Kwan; Hsiangting Chen; Xiao Tong; Lingyan Kong (Food Science and Human Wellness)
Microgreens are young and tender vegetables or herbs that provide attractive color, flavor, and nutrition. The purpose of this study was to evaluate the nutritional and sensory qualities of broccoli microgreens grown by different methods (hydroponically vs. soil grown) and from different sources (commercial vs. local farm). No significant difference in total phenolic concentration and antioxidant capacity was found in all broccoli microgreens, but a significantly higher chlorophyll concentration was found in farm microgreens than the commercial ones. Moreover, the soil-grown farm microgreens possessed a significantly higher vitamin C concentration than hydroponically-grown farm sample and commercial sample. Participants in the sensory study favored farm samples regardless of growing method, and their overall liking was significantly correlated with taste of the microgreens. In addition, six other microgreens from the local farm were analyzed for their nutritional quality. These conclusions suggested a potential for consumers to still benefit nutritionally by purchasing commercial microgreens at a lower cost; however, it may be worthwhile for consumers to purchase microgreens from local farms for a better sensory experience. Keywords: Microgreens, Antioxidant, Phenolic, Chlorophyll, Sensory, Hydroponics